2020
DOI: 10.14198/jhse.2022.172.16
|View full text |Cite
|
Sign up to set email alerts
|

Reception and performance in high level male volleyball: A relational study

Abstract: The aim of this study was to know the association of the reception zone on the performance of the reception of the high-performance male volleyball teams, considering the impact of rotation. The sample consist of 4223 KI sequences, belonging to 29 men's matches of world national teams of the highest level played between 2012 and 2016. The 3 main variables were: the rotation of the team in reception; the reception area; and the reception performance. For data analysis, Pearson's Chi-square analysis has been use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 29 publications
0
8
1
Order By: Relevance
“…RT2 * RZ5 also outperformed RT3 * RZ4, which would require the OHF to get closer to the net, limiting its spike run. López et al (2022), found a superior performance in reception after receiving in RT3 * ZR4 as compared to other rotations and back lines, while in this study we have found the opposite trend with a lower performance in the spike after receiving in this area. The use of short serves for strategic purposes trying to hinder the attack systems and reducing the performance of the teams in K1, has been raised by other authors in high-level men's volleyball (Lima et al, 2008;Maia & Mesquita, 2006).…”
Section: Discussioncontrasting
confidence: 67%
See 4 more Smart Citations
“…RT2 * RZ5 also outperformed RT3 * RZ4, which would require the OHF to get closer to the net, limiting its spike run. López et al (2022), found a superior performance in reception after receiving in RT3 * ZR4 as compared to other rotations and back lines, while in this study we have found the opposite trend with a lower performance in the spike after receiving in this area. The use of short serves for strategic purposes trying to hinder the attack systems and reducing the performance of the teams in K1, has been raised by other authors in high-level men's volleyball (Lima et al, 2008;Maia & Mesquita, 2006).…”
Section: Discussioncontrasting
confidence: 67%
“…This trend of decreased performance in spike after receiving the OHF was not observed in the previous situations, while it did occur in RT6 * RZ5. It is possible that in RT6 the highest percentage of serves made on the right side of the court (López et al, 2022), causes an imbalance of the reception structure towards that zone, generating a greater spatial responsibility in reception to the OHF both in RZ5 and in RZ61, which may hinder its transition to the spike. Similarly, lower performance was recorded in RT1 * RZ61.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations